1999
DOI: 10.1007/s004649901179
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a second-generation 3D endoscope on the laparoscopic precision of novices and experienced surgeons

Abstract: Second-generation 3D significantly improved the laparoscopic precision of novices and experienced surgeons, without the side effects reported from previous systems. This technology is expected to improve the ease and safety of laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(160 citation statements)
references
References 16 publications
6
151
1
2
Order By: Relevance
“…It was also the only determinant factor for performance in the first and easiest task. These findings confirm the important impact of binocular depth perception on surgical performance [1,8,19,25,26].…”
Section: Tasks Of Increasing Complexitysupporting
confidence: 82%
See 1 more Smart Citation
“…It was also the only determinant factor for performance in the first and easiest task. These findings confirm the important impact of binocular depth perception on surgical performance [1,8,19,25,26].…”
Section: Tasks Of Increasing Complexitysupporting
confidence: 82%
“…In laparoscopic surgery, new systems allow the use of two-(2D) or three-dimensional (3D) vision. However, the literature reports contradictory results concerning the benefits of 3D vision: some studies show that better motor performances are obtained with 3D vision [1,8,19,25,26] while others fail to reveal any difference in performance between 2D and 3D vision [5, 6, 12, 20]. In some studies [5], only complex tasks were performed faster and more easily with a 3D view whereas no difference between the use of 2D and 3D views appeared when performing the easiest tasks.…”
mentioning
confidence: 99%
“…Although some have reported that 3D imaging significantly improves performance, [2][3][4][5][6][7][8][9][10] others have claimed equivalency in task performance between 2D and 3D vision. 1,11,12 It is important that considerable technical advances have been made in the design of high-definition stereoscopic 3D visualization systems since the publication of these earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…In fact current endoscopic technology offers excellent resolution (high-definition [HD] cameras) but creates a two-dimensional (2-D) image that impairs depth perception and hand-eye coordination, and reduces the ability to estimate size. 7 To gain a depth cue in such a 2-D environment, surgeons seek sensorial and tactile feedback during manipulation of instruments by constantly moving the scopes in and out or from side to side. In this manner, depth perception is based on integration of indirect information from a variety of sources, including the surgeon's former knowledge of the spatial relationship between anatomical structures.…”
mentioning
confidence: 99%